Evaluation of Dynamic Compaction Load Conversion Methods and Vibration Reduction Treatments - Jixuan Li; Wenli Wang; Longping Luo; Xiaoliang Yao; Jiangang Hu (Buildings)
This study aims to evaluate the accuracy of different dynamic compaction (DC) load equivalent conversion methods in DC vibration calculations. It also investigates the effect of vibration isolation treatments on the vibration reduction performance of loess foundations, with the goal of optimizing vibration control during DC construction. Five classical methods were used to convert the DC loads into time-dependent surface loads, which were subsequently fed into Plaxis’s dynamic multiplier table for the numerical implementation of DC tests. By comparing the numerical simulation results with in situ monitoring data from a loess site, the accuracy of the five DC load equivalent conversion methods was evaluated. The momentum theorem method was identified as the most precise for both vibration velocity and settlement. Subsequently, the momentum theorem method was utilized to investigate the influence of depth and distance of vibration isolation trench, as well as the properties of vibration isolation materials on vibration reduction effect. It is indicated that the optimal depth for the vibration isolation trench of the loess site is 2 m, beyond which the improvement in vibration reduction effects is not notable. The excavation distance of the vibration isolation trench should be set as close as possible to the boundary of the construction site to achieve the best vibration reduction effect. As for the properties of vibration isolation materials, it is shown that the unit weight and damping ratio of the filling material have a significant effect on the vibration reduction effect, while the influence of the shear strength of the filling material is negligible. Besides the vibrating reduction influence of filling materials, utilizing spring dampers has a better vibration reduction effect. Increasing the stiffness of the spring dampers and reducing their spacing can significantly enhance the vibration reduction effect. In practical engineering applications, it is essential to consider both the effects and economic costs to select the optimal vibration reduction treatment and its parameters. This study provides a scientific basis for vibration control during DC construction, contributing to ensuring construction safety and efficiency while minimizing the impact on the surrounding environment.